Analisis Kebutuhan Kapasitas Fasilitas Sisi Darat Terminal Jangka Menengah Bandar Udara Internasional Pattimura Ambon - Gugat, Rudy Max Damara; Siahaan, L. Denny; Irenita, Novembriani; Hakia, Zulpa; Siregar, Rania Zahra (Institut Transportasi dan Logistik Trisakti, 2022)
The purpose of this study is to predict the growth of the number of passengers within 5 years, to know the need for the capacity of the facility in the planning year and to know the Level of Service (LOS) of the facility in the existing condition. This study uses multiple linear regression and facility performance to calculate the LOS value. The data used in this study are primary and secondary data. The results show that the percentage growth in the number of passengers in 2023-2027 has increased by 7% with the number of passengers in 2027 being 2,072,157 passengers. The calculation of the LOS value for the peak time of the existing condition based on the International Air Transport Association (IATA) standard the percentage of use of the existing condition curb resulted in the LOS D value with the percentage of space use 76%. The check-in area has LOS B value with a numerical value of 1.6 m2. The departure waiting room has LOS A with a numerical value of 2.1 m2. The baggage claim area has LOS C with a numerical value of 1.7 m2. For facility needs, there are 5 facilities with insufficient to accommodate passenger growth in the planning year (2027). These facilities are departure curb, departure hall, check-in area, baggage claim and toilet. Therefore, it is necessary to plan expansion improvements to improve performance at each facility.